2016
DOI: 10.4172/2155-9597.1000286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Staphylococcus aureus Infection on Biochemical and Antioxidant Activities of Fifth Instar Silkworm Larvae (Bombyx mori L.)

Abstract: In the present study silkworm used as a model animal for evaluating the pathogenicity of Staphylococcus aureus. The fifth instar silkworm larvae was used and infected by intrahaemocoelic injection of bacterial sample. The haemolymph was collected from the infected and control group larvae at 6, 12, 18 and 24 hours of post infection and stored at -4°C in eppendorf tubes to use. Lipid peroxidation, phenol oxidase and acid phosphatase activity were estimated in the haemolymph of control and infected group. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…As reported earlier, the pathogenic infection causes significant decrease in larval body weight, somatic index of silk gland tissue and weight of silk gland, which supports our findings 39,40 . A separate study on PPO activity in B. mori revealed that pathogenic infection leads to the immune induction via PPO activation cascade 41 .…”
Section: Changes In Physio-morpho-anatomical Responses In B Mori Duri...supporting
confidence: 93%
“…As reported earlier, the pathogenic infection causes significant decrease in larval body weight, somatic index of silk gland tissue and weight of silk gland, which supports our findings 39,40 . A separate study on PPO activity in B. mori revealed that pathogenic infection leads to the immune induction via PPO activation cascade 41 .…”
Section: Changes In Physio-morpho-anatomical Responses In B Mori Duri...supporting
confidence: 93%
“…Laevigata, which mean that larvae fed on M. alba var. Laevigata leaves may have more diseases tolerance or immunity because of the high level of phenoloxidase which lead to high tolerance response against pathogenic bacteria (Reddy and Venkatappa, 2016). The lysosomes was the main antibacterial factor responsible for immunity of vaccinated insects thus upon pathogens infection, antibacterial proteins, lysozymes rapidly appear in the haemolymph after infection with bacteria (Reddy et al, 2012) Experiments with three lepidopteran larvae of Galleria mellonella, Bombyx mori and Agrius convolvuli, similarly, have showed increased lysozyme activity upon immune challenging by Escherichia coli (Yu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%